ASSOCIATION AND COMPARISON OF PHYSICAL ACTIVITY WITH CARDIOVASCULAR HEALTH, QUALITY OF LIFE AND ANTHROPOMETRIC MEASUREMENTS IN ADULT WOMEN (CIPEEX, 2022)
CARDIOVASCULAR DISEASES (CVDS) ARE THE MAIN CAUSES OF DEATH IN THE WORLD AND THE MOST EFFECTIVE WAY TO REDUCE THE RISK FACTORS ASSOCIATED WITH THEM IS THE PRACTICE OF PHYSICAL ACTIVITY. THE OBJECTIVE OF THIS STUDY WAS TO ASSOCIATE AND COMPARE THE LEVEL OF PHYSICAL ACTIVITY WITH CARDIOVASCULAR HEALTH (CVH), QUALITY OF LIFE, CARDIORESPIRATORY FITNESS, ANTHROPOMETRIC VARIABLES AND WORKLOAD OF ACTIVE AND SEDENTARY WOMEN WORKING IN A UNIVERSITY ENVIRONMENT. IT IS A CROSS-SECTIONAL STUDY, CARRIED OUT WITH EMPLOYEES OF A HIGHER EDUCATION INSTITUTION. THE SAMPLE WAS FOR CONVENIENCE AND 51 HEALTHY ADULT WOMEN PARTICIPATED. SEVEN METRICS WERE EVALUATED FOR CVH, USING THE INTERNATIONAL PHYSICAL ACTIVITY QUESTIONNAIRE AND THE MEDITERRANEAN DIET QUESTIONNAIRE. QUALITY OF LIFE WAS ASSESSED USING THE SHORT FORM-36 INSTRUMENT AND CARDIORESPIRATORY FITNESS USING THE SHUTTLE RUN TEST. THE TESTS USED TO ANALYZE THE DATA WERE T-STUDENT TESTS, MANN-WHITNEY U TEST, AND A MULTIPLE LINEAR REGRESSION WAS PERFORMED WITH DATA ADJUSTED FOR AGE AND CLIMACTERIC. THE MAIN RESULTS INCLUDED THAT ACTIVE WOMEN HAD LOWER VALUES €‹€‹FOR WAIST-TO-HIP RATIO (WHR) (P=0.001), DIASTOLIC BLOOD PRESSURE (DBP) (P<0.001), WITH HIGHER RESULTS FOR MAXIMAL OXYGEN CONSUMPTION (VO2MAX) (P <0.001), CVH SCORE (P<0.001), FUNCTIONAL CAPACITY (P=0.004) AND GENERAL HEALTH (P=0.009). THERE WAS A DIRECT RELATIONSHIP WITH THE CVH SCORE (P=0.018), VO2MAX (P=0.012), WHILE IT WAS INVERSE FOR WORKLOAD (P=0.013). IN CONCLUSION, THE LEVEL OF PHYSICAL ACTIVITY CONTRIBUTES TO LOWER VALUES €‹€‹OF RISK FACTORS FOR CARDIOVASCULAR DISEASES (WHR AND DBP) AND HIGHER VALUES €‹€‹OF VO2MAX, CVH SCORES AND QUALITY OF LIFE IN ACTIVE WOMEN.
Keywords: physical activity; cardiovascular health; cardiovascular risk factors; quality of life